Research on cognitive abilities in untrained birds - Nácarová, Jana (Jihočeská univerzita, 2018)
This study investigates the cues used for predator recognition by wild-living untrained birds great tits (Parus major). The experimental approach is used to test the reaction to the variously modified dummies of sparrowhawk (Accipiter nisus) and pigeon (Columba livia f. domestica) under laboratory conditions. The role of key features (yellow eye, hooked beak and talons), colour and size is tested. The results imply that the presence of raptor-specific features is mostly necessary but not sufficient to recognize predator in the presented dummies. Following research revealed that the part of the variability in response of great tits can be taken on the account of personality.
Research on cognitive abilities in untrained birds
Keywords: Great tit; personality; cognition; predator recognition; Great tit; personality; cognition; predator recognition